Antibody-drug conjugates in the treatment of advanced triple-negative breast cancer - Kubiatowski, Tomasz; Kalinka, Ewa (Menopause Review/Przegląd Menopauzalny, 2025)
Triple-negative breast cancer accounts for approximately 15% of all diagnosed breast cancers and is characterized by an aggressive clinical course resulting from rapid proliferation of tumor cells poses a huge therapeutic challenge. The shortened, in comparison with other subtypes of breast cancer, progression free survival or the limited influence of the chemotherapy used on the overall survival imply the necessity of searching for new therapies. The use of monoclonal antibodies conjugated with a cytostatic initially allowed selective introduction of the drug into tumor cells showing expression of strictly defined receptor proteins on the cell membrane surface. Modification of the linkers binding the cytostatic to the antibody, on the other hand, allowed activation of the by-stander effect, allowing effective destruction of tumor cells lacking expression of specific antigens on their surface. Sacituzumab govitecan (anti-TROP2 antibody conjugated with inhibitor of topoisomerase I) improve median progression-free survival and overall survival in patients with advanced, metastatic triple-negative breast cancer. Similarly, a beneficial effect from the use of ADCs (trastuzumab deruxtecan) was observed in patients with low HER2 expression. These therapeutic advances are reflected in clinical guidelines from leading organizations such as ASCO and ESMO, and have become the basis for ongoing clinical trials evaluating new ADCs with different molecular targets and cytotoxic mechanisms. This paper reviews the most important studies evaluating the clinical effect of ADCs in the treatment of triple-negative breast cancer.